Firms, Informality and Development: Theory and evidence from Brazil - Gabriel Ulyssea (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2014)
This paper develops and estimates an equilibrium model where heterogeneous firms can exploit two margins of informality: (i) not register their business, the extensive margin; and (ii) hire workers "off the books", the intensive margin. The model encompasses the main competing frameworks for understanding informality and provides a natural setting to infer their empirical relevance. The counterfactual analysis shows that once the intensive margin is accounted for, aggregate firm and labor informality need not move in the same direction as a result of policy changes. Lower informality can be, but is not necessarily associated to higher GDP, TFP or welfare.
Keywords: O17; C54; O12; 330